Impact of N-acetylcysteine on the hepatic microcirculation after orthotopic liver transplantation - Koeppel, Thomas; Lehmann, Thorsten G.; Thies, Jochen; Gehrcke, Renate; Gebhard, Martha-Maria; Herfarth, Christian; Otto, Gerd; Post, Stefan (Transplantation, 1996)
Recent observations showed an improvement of hepatic macro- and microhemodynamics as well as survival rates after warm ischemia of the liver following treatment with N-acetylcysteine (NAC). In this study we assessed the influence of NAC on the hepatic microcirculation after orthotopic liver transplantation (OLT) using intravital fluorescence microscopy. OLT with simultaneous arterialization was performed in 16 male Lewis rats following cold storage in University of Wisconsin solution for 24 hr. Within the experimental group (n=8) donors received NAC (400 mg/kg) 25 min before hepatectomy. In addition, high-dose treatment of recipients with NAC (400 mg/kg) was started with reperfusion. Control animals (n=8) received an equivalent amount of Ringer's solution. Intravital fluorescence microscopy was performed 30-90 min after reperfusion assessing acinar and sinusoidal perfusion, leukocyte-endothelium interaction, and phagocytic activity. Treatment with NAC reduced the number of nonperfused sinusoids from 52.4±0.8% to 15.7±0.5% (P=0.0001) (mean ± SEM). Furthermore, we achieved a significant reduction of leukocytes adhering to sinusoidal endothelium (per mm2 liver surface) from 351.9±13.0 in controls to 83.6±4.2 in the experimental group (P=0.0001). In postsinusoidal venules, treatment with NAC decreased the number of sticking leukocytes (per mm2 endothelium) from 1098.5±59.6 to 425.9±37.7 (P=0.0001). Moreover, bile flow was significantly increased after therapy with NAC (4.3±1.2 vs. 2.2±0.7 ml/90 min × 100 g liver) (P<0.05). Phagocytic activity was not influenced by application of NAC. We conclude that high-dose therapy with NAC in OLT attenuates manifestations of microvascular perfusion failure early after reperfusion and should be considered as a means to reduce reperfusion injury.